2020
DOI: 10.3892/etm.2020.9248
|View full text |Cite
|
Sign up to set email alerts
|

Clinical investigation of acute myocardial infarction according to age subsets

Abstract: A growing number of 'Young' patients less than 40 years of age are being hospitalized with a diagnosis of acute myocardial infarction (AMI) due to increased prevalence of risk factors for atherosclerosis. The aim of this study was to compare clinical characteristics and performances of AMI between young and elderly patients. We conducted a retrospective study to compare AMI in young patients and elder patients. Based on the medical record databases in our hospital, we enrolled 114 'young' AMI patients (age ≤42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…In 2018, a retrospective study of the clinical data of 360 AMI patients treated in Peking Union Medical College Hospital found that most AMI patients under the age of 30 were acute ST-segment elevation myocardial infarction, with single and nonobstructive lesions common, and the anterior descending branch was the most common criminal vessel [ 4 ]. This reveals the clinical and coronary artery lesion characteristics of patients with acute myocardial infarction under the age of 30.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, a retrospective study of the clinical data of 360 AMI patients treated in Peking Union Medical College Hospital found that most AMI patients under the age of 30 were acute ST-segment elevation myocardial infarction, with single and nonobstructive lesions common, and the anterior descending branch was the most common criminal vessel [ 4 ]. This reveals the clinical and coronary artery lesion characteristics of patients with acute myocardial infarction under the age of 30.…”
Section: Introductionmentioning
confidence: 99%
“…The nomogram in our study showed that being older was a risk factor for AMI. Using coronary angiography results, Wang et al 23 found that the most frequent coronary lesion in young patients with AMI was lesions with one branch (62.4%) and secondary injury was limited. These authors also found that older patients with AMI had more multiple branch lesions and calcified lesions, which had a serious effect on cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the lack of an accurate scoring system for AMI patients, 4610 patients and 30 risk factors relating to AMI were selected using sample data from the MIMIC-III database [14][15][16][17][18]. Using a random forest [19] selection method identi ed 19 risk factors that had been identi ed in the multivariate logistic regression analysis [20].…”
Section: Discussionmentioning
confidence: 99%